A closer look at the in vitro electrochemical characterisation of titanium alloys for biomedical applications using in-situ methods. (May 2017) - Wang, J.-L.; Liu, R.L.; Majumdar, T.; Mantri, S.A.; Ravi, V.A.; Banerjee, R.; Birbilis, N.
Graphical abstract: Abstract: Titanium (Ti) and its alloys are widely used in several biomedical applications, particularly as permanent orthopaedic implants. Electrochemical testing provides a means to perform accelerated corrosion testing, however whilst results from polarisation testing for Ti and its alloys to date have been generally useful, they are also rather limited on the basis of several reasons. One reason is that the polarisation curves for Ti and its alloys in simulated body fluids all appear rather similar, and they do not present a classical 'breakdown' or pitting potential, making discrimination between alloys difficult. Of practical relevance however, are two key issues; (1) how do Ti alloys respond to a breakdown event? (i.e. do they readily 'repassivate'?), and, (2) what is that actual rate of Ti ion loss from exposure to physiological conditions? The answers to these questions are probed herein. Several Ti alloys of either unique composition or different fabrication method were studied, including commercially pure Ti (cp-Ti), Ti-6Al-4V, Ti-29Nb-13Ta-4.5Zr (TNTZ), selective laser melted Ti-6Al-4V, direct laser deposited cp-Ti, Ti-35Nb-15Zr, and Ti-25Nb-8Zr. Results reveal that both fabrication method and alloying influence 'repassivation' behaviour. Furthermore, atomic emission spectroelectrochemistry as applied to cp-Ti indicated actual dissolution currents of ∼2–3 μA/cm −2 (i.e. ∼9 μm/yr) in the range of the corrosion potential, also revealing such dissolution is persistent, even with cathodic polarisation, and definitively revealing that the presence of hydrogen peroxide and albumin activate anodic dissolution of Ti. Statement of Significance: We believe the paper makes a significant and important contribution to the field of permanent implant biomaterials. Whilst we concede that the paper does not include any in vivo work, the timeliness of the work, and the completely new nature of the findings, we believe carries the impact required for Acta Biomaterialia . Key highlights include: - A means of assessment of 'repassivation' of Ti-alloys used as biomaterials (for the first time). - Reportage of the performance of various Ti-alloys fabricated by 3D printing (for the first time). - The first unambiguous reporting of the TRUE corrosion rate of Ti in biological environments, employing the advanced AESEC method (for the first time). - Demonstration of the real, and important, effect of the combination of albumin and H2 O2 upon dissolution kinetics of Ti (recently revealed to be critically important in this journal: F. Yu, O. Addison, A.J. Davenport, A synergistic effect of albumin and H2 O2 accelerates corrosion of Ti6Al4V, Acta Biomater, 26 (2015) 355–365) All of the above combine to produce a manuscript that we believe has wide appeal, and can be used as both a port of reference to those working with Ti biomaterials, and also those wishing to apply useful characterisation techniques to their own work (with two very novel methods demonstrated herein, along with the unique information they provide).